2021
DOI: 10.1002/ps.6269
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol‐based terpenoids as promising bio‐sourced crop protection compounds against the wheat pathogen Zymoseptoria tritici

Abstract: BACKGROUND Research into environmentally friendly alternatives to conventional plant protection products, to promote sustainable agriculture and healthy food, is strongly encouraged. RESULTS In this context, 20 naturally occurring terpenoids and phenolic compounds were selected and evaluated in vitro as crop protection compounds against Zymoseptoria tritici, the causal agent of Septoria tritici blotch of wheat. After selection of the most active compounds, some hemisynthetic modifications were conducted to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…There are no striking differences in anticandidal potential of the homologues higher than C 3 , and from the Table 2 we can notice that there is anticandidal activity evidenced in all of the synthesized compounds (3a-y). Interestingly, Damiens et al 36 have observed and stated the importance of (a balanced) hydrophilicity/lipophilicity ratio, though in sesamol derivatives, against a phyto-pathogen fungi Zymoseptoria tritici (modulating lipophilicity proved to increase the antifungal biological activity for sesamol derivatives). The phenomena noticed in our research and in Damiens et al 36 does not have to be an isolated incident, it could also be a regularity based on subtle structural changes that would, within certain limits, by enhancing lipophilicity affect bioactivity.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no striking differences in anticandidal potential of the homologues higher than C 3 , and from the Table 2 we can notice that there is anticandidal activity evidenced in all of the synthesized compounds (3a-y). Interestingly, Damiens et al 36 have observed and stated the importance of (a balanced) hydrophilicity/lipophilicity ratio, though in sesamol derivatives, against a phyto-pathogen fungi Zymoseptoria tritici (modulating lipophilicity proved to increase the antifungal biological activity for sesamol derivatives). The phenomena noticed in our research and in Damiens et al 36 does not have to be an isolated incident, it could also be a regularity based on subtle structural changes that would, within certain limits, by enhancing lipophilicity affect bioactivity.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Interestingly, Damiens et al 36 have observed and stated the importance of (a balanced) hydrophilicity/lipophilicity ratio, though in sesamol derivatives, against a phyto-pathogen fungi Zymoseptoria tritici (modulating lipophilicity proved to increase the antifungal biological activity for sesamol derivatives). The phenomena noticed in our research and in Damiens et al 36 does not have to be an isolated incident, it could also be a regularity based on subtle structural changes that would, within certain limits, by enhancing lipophilicity affect bioactivity. It is certain that this aspect deserves further research.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-synthetic rhamnolipids (RLs) were active on Z. tritici (Platel et al, 2020). Semi-synthetic sesamol esters displayed high activity against Z. tritici (Damiens et al, 2021). Effusol, a 9,10-dehydrophenanthrene natural product from rhizomes of the plant Juncus maritimus, is active against Z. tritici (Sahli et al, 2018).…”
Section: S Tritici Blotch Control Using Fungicidesmentioning
confidence: 99%
“…Nevertheless, each use was based on the fine composition of essential oils and large variability occurred. It is also known that biological activity depends on the chemical composition of the EOs [34,35]. Most of the time, the main components are important, but sometimes synergic effects due to the different, eventually minor, compounds can lead to surprising enhanced (or decreased) biological activities.…”
Section: Introductionmentioning
confidence: 99%